Continuous EEG monitoring: A survey of neurophysiologists and neurointensivists. Issue 11 (29th September 2014) - Gavvala, Jay; Abend, Nicholas; LaRoche, Suzette; Hahn, Cecil; Herman, Susan T.; Claassen, Jan; Macken, Mícheál; Schuele, Stephan; Gerard, Elizabeth; the Critical Care EEG Monitoring Research Consortium (CCEMRC)
Summary Objective Continuous EEG monitoring (cEEG) of critically ill adults is being used with increasing frequency, and practice guidelines on indications for cEEG monitoring have recently been published. However, data describing the current practice of cEEG in critically ill adults is limited. We aimed to describe the current practice of cEEG monitoring in adults in the United States. Methods A survey assessing cEEG indications and procedures was sent to one intensivist and one neurophysiologist responsible for intensive care unit (ICU) cEEG at 151 institutions in the United States. At some institutions only one physician could be identified. Results One hundred thirty‐seven physicians from 97 institutions completed the survey. Continuous EEG is utilized by nearly all respondents to detect nonconvulsive seizures (NCS) in patients with altered mental status following clinical seizures, intra cerebral hemorrhage (ICH), traumatic brain injury, and cardiac arrest, as well as to characterize abnormal movements suspected to be seizures. The majority of physicians monitor comatose patients for 24–48 h. In an ideal situation with unlimited resources, 18% of respondents would increase cEEG duration. Eighty‐six percent of institutions have an on‐call EEG technologist available 24/7 for new patient hookups, but only 26% have technologists available 24/7 in‐house. There is substantial variability in who reviews EEG and how frequently it is reviewed as well as use of quantitative EEG. Significance Although there is general agreement regarding the indications for ICU cEEG, there is substantial interinstitutional variability in how the procedure is performed.